Anti-mitotic Activity of Bleomycin: Time of Action in the Mammalian Cell Cycle - Wheatley, D. N. (Nature Publishing Group, 1974)
Bleomycin inhibits cell division in HeLa S-3 and other mammalian epithelial cell lines. Its effect on suspension cultured cells is far greater than on monolayer cells; this was found to be due partly to the absence of divalent ions. Other mammalian epithelial lines in suspension culture are very sensitive but fibroblastic cells (BHK 21/C13/DWS-3) grown under identical conditions are relatively insensitive. This study has established that bleomycin is a powerful anti-mitotic agent during the G(2) phase but it does not prevent prophase cells from completing a normal mitotic division. Its ability to suppress DNA synthesis contributes little to the inhibition of cell cycling.